Stochastic wave packets of natural oscillatory systems - Грицунов, А. В.; Бондаренко, И. Н.; Близнюк, И. Ю. (Харьковский национальный университет радиоэлектроники, 2017)
De Broglie waves are interpreted as oscillations of generalized coordinates of natural oscillatory systems with distributed parameters (NOSs). The action four-scalar and the momentum- energy four-vector both are assimilated with the geometry of NOS eigenmodes in the Minkowski spacetime. A conservation law for the action is supposed as a necessary condition for the energy-momentum conservation. The Wheeler-Feynman’s concept of “direct interparticle action” is developed for both the quantum radiation-absorption and the Coulomb interaction. The spatio-temporal localization of NOS wave packets and Heisenberg’s “uncertainty principle” both are assumed to be results of stochastic exchange with action quanta between different NOSs. The simplest examples of NOS wave packets are given. Some outcomes of application of this theory to solid state phenomena are discussed.
Keywords: De Broglie waves; natural oscillatory systems; stochastic wave packets